Vogesella urethralis sp. nov., isolated from human urine, and emended descriptions of Vogesella perlucida and Vogesella mureinivorans. Issue 1 (3rd February 2020) - Lan, Kai; Cai, Yi-Mei; Li, Liang-Hui; Zeng, Jian-Ming; Yu, Xue-Gao; Qu, Ping-Hua; Li, Hong-Lin; Liu, Yu-Yang; Chen, Liang; Chen, Cha; Huang, Bin
Abstract : A novel Vogesella strain, YM-1 T, was recovered from human urine in PR China in 2017. Cells of strain YM-1 T were Gram-stain-negative, rod-shaped, aerobic, motile, non-spore-forming and poly-β-hydroxybutyrate-accumulating. The strain contained C16:1 ω6 c /C 16:1 ω7 c, C16:0 and C18:0 ω7 c as major fatty acids; phosphatidylethanolamine, phosphatidylglycerol, diphosphatidylglycerol and an unidentified phospholipid as major polar lipids; and ubiquinone-8 as the predominant respiratory quinone. Comparison of 16S rRNA gene sequences indicated that this strain had highest similarities to Vogesella perlucida DS-28 T (98.8 %) and Vogesella mureinivorans 389 T (98.1 %). The results of phylogenetic analysis based on the 16S rRNA gene sequences revealed that the novel strain was clustered and well separated with V. perlucida DS-28 T and V. mureinivorans 389 T within the genus Vogesella . The average nucleotide identity (ANI) and amino acid identity (AAI) analyses showed that this strain was not identified as V. perlucida DS-28 T or V. mureinivorans 389 T, with values well below the threshold limit for species demarcation (ANI <88.1 %, AAI <88.6 %). Based on the above results, strain YM-1 T is proposed to be a novel species of the genus Vogesella with the name Vogesella urethralis sp. nov. (YM-1 T =NBRC 113779=CGMCC 1.17135).